Genetic aspects of congenital heart disease in heterotaxy syndromeAspetos genéticos da cardiopatia congénita na síndrome de heterotaxia - Ahmad Rafie, Nur Nabihah; Yubbu, Putri; Aissvarya, Shankar; Pujita, Rajendran; Musa, Nurul Huda; Mohamed Ibrahim, Noor Haliza; Thilakavathy, Karuppiah (Sociedade Portuguesa de Cardiologia, 2025)
Abnormal arrangement of thoracoabdominal organs, situs ambiguous, is also known as heterotaxy syndrome (HTX). It has been frequently linked with congenital heart diseases (CHD), which are commonly reported as atrioventricular septal defects (AVSD), atrial septal defects (ASD), ventricle septal defects (VSD), transposition of the great artery, and pulmonary stenosis or atresia. Two HTX categories are right atrial isomerism (RAI) and left atrial isomerism (LAI), which are distinguished by the organ's sidedness as well as their complexity. The etiology of the syndrome is being studied widely, where recent studies are more focused on the effect of gene variants present in affected individuals. DNAH11, DNAH5, ZIC3, NODAL, and LEFTY are among the genes studied and associated with HTX. DNAH11 and DNAH5 are associated with ciliary function while ZIC3, NODAL and LEFTY are associated with signaling pathways. As multiple genes are involved, HTX has been reported to have an autosomal dominant, autosomal recessive or X-linked inheritance patterns, depending on the causative genes in the individual. This review aims to summarize several previously reported HTX gene variants, inheritance patterns, as well as the cardiac and extracardiac clinical manifestations.